Effects of Different Diluents on Semen Quality of Hu Ram Stored at 4 °C - Liuming Zhang; Yanhu Wang; Xiaomei Sun; Yan Kang; Tariq Sohail; Jian Wang; Yongjun Li (Animals, 2023)
This study aimed to investigate the effects of various diluents on the quality of Hu ram sperm stored at 4 °C. Semen samples were collected from three Hu rams and diluted with diluents A (Sodium citrate–Glucose–Egg yolk), B (Sodium citrate–Glucose), C (Fructose–Skimmed milk powder–Soy lecithin), and D (Tris–Fructose–Citric acid–Egg yolk). Total motility (TM), straight-line velocity (VSL), average path velocity (VAP), curvilinear velocity (VCL), average motion degree (MAD), acrosome integrity, membrane integrity, and reactive oxygen species (ROS) were evaluated. The results showed that diluent D had better preservation in terms of the sperm TM, VSL, VCL, VAP, MAD, and membrane and acrosome integrity. On the third day of the storage, the sperm PM of diluent D was higher than that of other diluents (p < 0.05). The ROS level of diluent D was lower than that of other diluents on the fifth day (p < 0.05). On the seventh day of the storage, the sperm TM in diluent D reached 50%, which was the highest in all diluent groups. On the seventh day of the storage, the integrity of the sperm membrane and the integrity of the acrosome of the sperm in diluent D were the highest in all diluent groups (p < 0.05). In conclusion, these results indicated that diluent D improved the semen quality during storage at 4 °C. In this study, diluent D was the best diluent formula for Hu ram semen stored at 4 °C.